Parametric studies in the gasification agent and fluidization velocity during oxygen-enriched gasification of biomass in a pilot-scale fluidized bed: Experimental and numerical assessment. (March 2020) - Ismail, Tamer M.; Ramos, Ana; Monteiro, Eliseu; El-Salam, M. Abd; Rouboa, Abel
Abstract: The need to achieve renewable alternatives for energy production is pressing and new technologies have been developed. Biomass is a feasible feedstock for thermal conversion techniques like gasification. This technique converts carbonaceous fuels into energy, producing a synthetic gas (syngas) with further commercial uses such as electricity generation, fuels or the chemical industry among others. In this work, a numerical model was developed in order to optimize the experimental parameters in the gasification of agricultural residues. Hence, oxygen content (OC) in the gasifying agent, equivalence ratio (ER) and fluidization velocity were varied so as to assess the effect of each parameter in syngas quality. Lower ER favored higher CO and H2 yields, enhancing also the lower heating value (LHV). Higher fluidization velocity also promoted these features, as well as gasification conversion efficiency (GCE) and carbon conversion efficiency (CCE). Higher OC in the gasifying agent improve syngas quality. The optimal gasification performance was achieved for OC = 40%. The results obtained in this work are essential to describe scenarios relating to the potential use of agricultural residues as a source of energy via gasification. Highlights: Experimental biomass gasification is performed in a pilot-scale fluidized bed. A homemade CFD model for biomass gasification is proposed. The model is capable of predicting the syngas composition under different conditions. The effect oxygen content and fluidization velocity on gasification is disclosure.